2002
DOI: 10.1080/00908310290086554
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Extremophiles for Biotechnological and Petroleum Applications

Abstract: The ability of microorganisms to survive under harsh conditions has recently prompted researchers to study these microbes to better understand their characteristics and eventually utilize them in various applications. Extremophilic microorganisms withstand one or more extreme condition constraints due to cold, heat, high acidity, high alkalinity, high salinity, and high pressure levels. These constraints would destroy normal microorganisms. Extremophiles can be classi ed according to the environment in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 50 publications
0
24
0
4
Order By: Relevance
“…In comparison to non-petroleum oils, numerous works has been done to study the environmental factors influencing the biodegradation of petroleum hydrocarbons in marine waters (Atlas and Bartha, 1972;Atlas and Bartha, 1973;Siron et al, 1995;Sharma and Pant, 2000;Tango and Islam, 2002). The processes of spreading, evaporation, dispersion, emulsification and dissolution are most important during the early stages of a spill whilst oxidation, sedimentation and biodegradation are more important later on and determine the ultimate fate of the oil (Blumer et al, 1973).…”
Section: M Al-darbi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to non-petroleum oils, numerous works has been done to study the environmental factors influencing the biodegradation of petroleum hydrocarbons in marine waters (Atlas and Bartha, 1972;Atlas and Bartha, 1973;Siron et al, 1995;Sharma and Pant, 2000;Tango and Islam, 2002). The processes of spreading, evaporation, dispersion, emulsification and dissolution are most important during the early stages of a spill whilst oxidation, sedimentation and biodegradation are more important later on and determine the ultimate fate of the oil (Blumer et al, 1973).…”
Section: M Al-darbi Et Almentioning
confidence: 99%
“…Nevertheless, hydrocarbon-degrading microorganisms have adapted to grow and thrive in these environments and play an important role in recovery of polluted extreme habitats (Margesin and Schinner, 2001). Seawater contains a range of microorganisms that can partially or completely degrade oil to water-soluble compounds and eventually to carbon dioxide and water (Dean-Raymond and Bartha, 1975;Tango and Islam, 2002).…”
Section: M Al-darbi Et Almentioning
confidence: 99%
“…In another method, water containing a source of vitamins, phosphates, and electron acceptors such as nitrate, is injected into the reservoir, so that anaerobic bacteria can grow by using oil as the main carbon source (Sen, 2008). The microorganisms used in MEOR methods are mostly anaerobic extremophiles, including halophiles, barophiles, and thermophiles for their better adaptation to the oil reservoir conditions (Brown, 1992;Khire & Khan, 1994;Bryant & Lindsey, 1996;Tango & Islam, 2002). These bacteria are usually hydrocarbon-utilizing, non-pathogenic, and are naturally occurring in petroleum reservoirs (Almeida et al 2004).…”
Section: Miscible Displacement Processesmentioning
confidence: 99%
“…Many metallotolerant microbes may play an important role in the biogeochemical cycling of toxic heavy metals (21,22). They could be new resources for active biosorbents of heavy metals and could have several applications in bioremediation of metal-polluted sites.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency of appearance of bacteria resistant to specific heavy metal can be used as biological monitors of environmental contamination. It was reported that thermophilic microorganisms in particular, due to their unique metabolic properties and cell wall structure, could be prospective in biotechnological application (9,10,21).…”
Section: Introductionmentioning
confidence: 99%